2017
DOI: 10.1126/sciadv.1600821
|View full text |Cite
|
Sign up to set email alerts
|

The last frontiers of wilderness: Tracking loss of intact forest landscapes from 2000 to 2013

Abstract: Intact forest landscapes have the greatest conservation value but are shrinking due to industrial logging and fragmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
540
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 630 publications
(614 citation statements)
references
References 42 publications
10
540
0
12
Order By: Relevance
“…These metrics do not include expansion into agroforests, which have been identified as a major source of expansion in previous studies. One global study focused on intact forests landscapes, and suggested that oil palm accounted for a negligible amount (0.2%) of forest clearing in tropical regions (496,497).…”
Section: Resultsmentioning
confidence: 99%
“…These metrics do not include expansion into agroforests, which have been identified as a major source of expansion in previous studies. One global study focused on intact forests landscapes, and suggested that oil palm accounted for a negligible amount (0.2%) of forest clearing in tropical regions (496,497).…”
Section: Resultsmentioning
confidence: 99%
“…Also indicated are boundaries for all major watersheds, and political jurisdictions (inset right). [31]; 5 Approximate population density based on Instituto Nacional de Estadística (Chile) [32] and estimated population from cities and villages (Argentina). …”
Section: Study Areamentioning
confidence: 99%
“…They are essential in terms of conserving biodiversity, climate change mitigation, or as reference systems for forest management or restoration [3]. Global inventories and mapping efforts focused on forest integrity have proliferated given the concerns on the rapid decline of primary forests [4,5]. These efforts include global distribution analyses of intact forest landscapes by biome [5], estimated rate of change of forest cover [4], levels of forest fragmentation [6], global human footprint [7,8], and areas prioritized for potential restauration [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Afromontane and old-growth forests are remotely located and owned by the state, which make them difficult for the public to access. This is a consequence of the decline of natural forest from 40% to 3% during the 20th century [68,69], which is a process that is continuing in Ethiopia. At the same time, agroforestry homegardens and agroforestry shade-grown coffee are widely distributed in the study area.…”
Section: Multiple Ecosystem Services From Priority Land Covers For Rumentioning
confidence: 99%